Bytový dům - Novotný, Patrik (Vysoké učení technické v Brně. Fakulta stavební, 2021)
Bytový dům se nachází na mírném svahu v?oblasti Brno – sadová. Objekt má 4 nadzemní podlaží a 1 podzemní podlaží s?celkovým počtem 13 bytovými jednotkami a suterénem. Převládající bytové jednotky jsou 1+kk. Bytový dům je navržen jako kombinovaný stěnový konstrukční systém s?převládajícím příčným stěnovým systémem z?vápenopískových tvárnic a stropem z montovaných dílců. Bytový dům má navržené základové pasy z?prostého betonu. Jelikož na pozemku se nachází nepropustná zemina je zde navržen drenážní systém okolo celého objektu. Na objektu se nachází jednoplášťová vegetační plochá střecha s?využitím pro rekreaci obyvatel bytu v?4.NP.

This apartment house is located on a slightly steep hillside in the area brno-sadová. The building is composed of 4 above-ground floors and 1 underground floor, including total 13 apartments and 1 basement. Most of the apartments are one room + kitchen corner. The apartment house is designed as a combined wall construction system with a dominant cross walls setup, which is consisted of chalk-sand breeze blocks and the assembled-parts ceiling. The apartment house has a wall footing made of a simple concrete. Due to the the impervious soil presence on the whole land, the drainage system was built around the whole place. There is a single layer, vegetational flat roofing on the building, which among other things serves as a recreative zone for residents living in the fourth above-ground floor.
Apartment building
Keywords: Bytový dům; projektová dokumentace pro provedení stavby; vegetační střecha; vnější kontaktní zateplovací systém; Apartment house; design documentation for construction; green roof; external thermal insulation composite system